Henry VIII's will: the protectorate provisions of 1546–7 - Ives, Eric W. (The historical journal, 1994)
Dr Houlbrooke's overall acceptance of the genuineness of Henry VIII's will is welcomed but his hypothesis about the protectorate is qualified, (i) Paget's testimony is shown not to indicate that the ‘gifts clause’ was added to the will after 12 January 1547. (ii) Corrections to the paper which underlies Paget's statement suggest that the distribution of honours under the clause related to Henry's wish to establish the Seymour faction, not to support for the protectorate. (iii) Moves towards the latter were only implemented when Henry's death was imminent, (iv) There is a plausible case to suspect jobbery then and (v) at the stage of the second protectorate, (vi) It is argued that in interpreting Henry's will, we must see (a) faction as intrinsic to court politics and (b) Henry VIII's religious policy as inherently and-traditional.